2017
DOI: 10.1039/c6ta07541j
|View full text |Cite
|
Sign up to set email alerts
|

Cerium oxide standing out as an electron transport layer for efficient and stable perovskite solar cells processed at low temperature

Abstract: Low-temperature, solution-processed cerium oxide can serve as a promising electron transport layer to replace commonly used TiO2 in planar perovskite solar cells, with high efficiency and enhanced stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(91 citation statements)
references
References 55 publications
2
87
0
Order By: Relevance
“…9,33 Meanwhile, the high cost of high-purity organic semiconductor electron transfer materials also make them unaffordable to large scale industrial photovoltaic application. 34 Very recently, Ke and Wang employed the SnO 2 and CeO x as ETL in PSCs via solution-processed with a PCE of 17.21%, 14.3%, respectively, 35,36 however, the processing temperature are near to $150 C, which will limit the application in exible substrates. WO x and In 2 O 3 are also applied in the PSCs for electrons transportation at a low synthesis temperature with a low PCE of 8.99% and 13.01%, respectively.…”
Section: 28mentioning
confidence: 99%
“…9,33 Meanwhile, the high cost of high-purity organic semiconductor electron transfer materials also make them unaffordable to large scale industrial photovoltaic application. 34 Very recently, Ke and Wang employed the SnO 2 and CeO x as ETL in PSCs via solution-processed with a PCE of 17.21%, 14.3%, respectively, 35,36 however, the processing temperature are near to $150 C, which will limit the application in exible substrates. WO x and In 2 O 3 are also applied in the PSCs for electrons transportation at a low synthesis temperature with a low PCE of 8.99% and 13.01%, respectively.…”
Section: 28mentioning
confidence: 99%
“…They reported that this CeO x (x = 1.87) based electron transport material can be processed at low temperatures and is equally efficient for electron extraction from perovskite absorber layer. Stability test showed that this material is more robust as compared to conventional TiO 2 based ETL [159]. They also improvised a buffer layer of PC 61 BM between ETL and absorber to enhance the UV stability.…”
Section: By Altering the Perovskite Materialsmentioning
confidence: 99%
“…Moreover,e fficient hole-blocking capacity is also necessary fora ne ffective ESL. These metal oxides include TiO 2 , [18] SnO 2 , [19,20] ZnO, [21,22] WO x , [23,24] Fe 2 O 3 , [5] CeO 2 , [25] Nb 2 O 5 , [26] and derivativess uch as BaSnO 3 , [27] Zn 2 SnO 4 , [28] Mg-doped metal oxides, [29] Nb-doped metal oxides, [24,30] and La-doped metal oxides. To date, the widely used ESL materials can be roughly divided into four categories: fullerene-based materials, [8][9][10] n-type conjugated polymers, [11,12] metal oxides, and metal chalcogenides.…”
Section: Introductionmentioning
confidence: 99%